Evaluation of the impact of women on health in Curridabat (Tirrases), San Jose, Costa Rica - Delfina Charlton Lewis (Universidad de Alicante, 2012)
A qualitative research was carried out in Curridabat (Tirrases, Costa Rica) by 10 leader women whose aim was helping their community to improve health conditions, achieve women empowerment, autonomy and adequate decision making, taking in consideration social, political and economical aspects. Three group sessions dealt with health determining factors in the social, political and economical areas respectively. Later, according to the objectives, a qualitative data analysis was performed and the results are presented in this work.